Transcellular water flow modulates water channel exocytosis and endocytosis in kidney collecting tubule. - Kuwahara, M (1991)
The regulation of osmotic water permeability (Pf) by vasopressin (VP) in kidney collecting tubule involves the exocytic-endocytic trafficking of vesicles containing water channels between an intracellular compartment and apical plasma membrane. To examine effects of transcellular water flow on vesicle movement, Pf was measured with 1-s time resolution in the isolated perfused rabbit cortical collecting tubule in response to addition and removal of VP (250 microU/ml) in the presence of bath greater than lumen (B greater than L), lumen greater than bath (L greater than B), and lumen = bath (L = B) osmolalities. With VP addition, Pf increased from 12 to 240-270 x 10(-4) cm/s (37 degrees C) in 10 min. At 1 min, Pf was approximately 70 x 10(-4) cm/s for B greater than L, L greater than B, and L = B conditions. At later times, Pf increased fastest for L greater than B and slowest for B greater than L osmolalities; at 5 min, Pf was 250 x 10(-4) cm/s (L greater than B) and 158 x 10(-4) cm/s (B greater than L). With VP removal, Pf returned to pre-VP levels at the fastest rate for B greater than L and the slowest rate for L greater than B osmolalities; at 30 min, Pf was 65 x 10(-4) cm/s (B greater than L) and 183 x 10(-4) cm/s (L greater than B). For a series of osmotic gradients of different magnitudes and directions, the rates of Pf increase and decrease were dependent upon the magnitude of transcellular volume flow; control studies showed that paracellular water flux, asymmetric transcellular water pathways, or changes in cell volume could not account for the data. VP-dependent endocytosis was measured by apical uptake of rhodamine-dextran; in paired studies where the same tubule was used for + and - gradients, B greater than L and L greater than B osmolalities gave 168% and 82% of uptake measured with no gradient. In contrast, endocytosis in proximal tubule was not dependent on gradient direction. These data provide evidence that transcellular volume flow modulates the vasopressin-dependent cycling of vesicles containing water channels, suggesting a novel driving mechanism to aid or oppose the targeted, hormonally directed movement of subcellular membranes.